2015
DOI: 10.3389/fnhum.2015.00176
|View full text |Cite
|
Sign up to set email alerts
|

Age-related striatal BOLD changes without changes in behavioral loss aversion

Abstract: Loss aversion (LA), the idea that negative valuations have a higher psychological impact than positive ones, is considered an important variable in consumer research. The literature on aging and behavior suggests older individuals may show more LA, although it is not clear if this is an effect of aging in general (as in the continuum from age 20 and 50 years), or of the state of older age (e.g., past age 65 years). We also have not yet identified the potential biological effects of aging on the neural processi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 85 publications
(153 reference statements)
2
18
0
Order By: Relevance
“…Second, we calculated the Shannon entropy (i.e., information; see Shannon and Weaver, 1949 ) of the distribution of keypress counts to approach ( H + ) or avoid ( H − ) the face stimuli within each category. Keypress measures of value such as those reported here have also been studied in the context of neuroimaging data, and have been specifically linked to activation of reward circuitry (Aharon et al, 2001 ; Strauss et al, 2005 ; Perlis et al, 2008 ; Gasic et al, 2009 ; Viswanathan et al, 2015 ) that appears affected by genotype (Perlis et al, 2008 ; Gasic et al, 2009 ). In addition, pattern variables such as Shannon entropy have been shown to be important metrics for quantifying neural processing (Viola et al, 1996 ; Rieke, 1997 ; Tiesinga et al, 2002 ; Reeke and Coop, 2004 ), and define the “information” that is processed in cognitive neuroscience (Breiter et al, 2006 ; Kim et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Second, we calculated the Shannon entropy (i.e., information; see Shannon and Weaver, 1949 ) of the distribution of keypress counts to approach ( H + ) or avoid ( H − ) the face stimuli within each category. Keypress measures of value such as those reported here have also been studied in the context of neuroimaging data, and have been specifically linked to activation of reward circuitry (Aharon et al, 2001 ; Strauss et al, 2005 ; Perlis et al, 2008 ; Gasic et al, 2009 ; Viswanathan et al, 2015 ) that appears affected by genotype (Perlis et al, 2008 ; Gasic et al, 2009 ). In addition, pattern variables such as Shannon entropy have been shown to be important metrics for quantifying neural processing (Viola et al, 1996 ; Rieke, 1997 ; Tiesinga et al, 2002 ; Reeke and Coop, 2004 ), and define the “information” that is processed in cognitive neuroscience (Breiter et al, 2006 ; Kim et al, 2010 ).…”
Section: Introductionmentioning
confidence: 99%
“…The approach/avoidance task (Kim et al, 2010 ) gauged to what extent subjects would actively keypress to increase or decrease the amount of time they were exposed to face stimuli belonging to four categories: non-model male, non-model female, model male, and model female faces (Aharon et al, 2001 ). This validated task (Aharon et al, 2001 ; Elman et al, 2005 ; Strauss et al, 2005 ; Levy et al, 2008 ; Perlis et al, 2008 ; Gasic et al, 2009 ; Yamamoto et al, 2009 ; Kim et al, 2010 ; Viswanathan et al, 2015 ) quantified the effort subjects were willing to expend to approach or avoid each face stimulus. We then computed metrics that quantified the magnitude and predictability of the participants' keypress behavior.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent fMRI study, no relationship has been observed between age and LA, but an increasing neural differential sensitivity of the Ventral Striatum (VS)/Nucleus Accumbens (NAc) to avoidance responses (negative valuations) relative to approach responses (positive valuations) has been evidenced with aging. These findings suggest that a central region for reward/aversion processing (VS/NAc) changes with age [ 27 ]. The same cerebral regions involved in the reward/aversion system, such as the NAc, caudate, and putamen, are also engaged in reaction to humoristic stimuli [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Aging‐related dysfunction of the reward system may be a contributor. The brain's reward system, comprised by the amygdala, ventral tegmental area, nucleus accumbens, ventral striatum, medial prefrontal cortex, and orbitofrontal cortex, is particularly susceptible to the effects of aging evidenced by microstructural changes in white matter and in functional connectivity . These neural abnormalities are strongly associated with disrupted reward‐related behaviors during aging .…”
Section: Discussionmentioning
confidence: 99%